THE CORRELATION BETWEEN READINGANXIETY AND READING COMPREHENSION AT SMA NEGERI 3 BAUBAU - Husni, Husni; Una, Syamsul; Yusri, Yusri (English Education Journal, 2024)
The formulation of the problem in this research is whether there is a significant relationship between students' reading anxiety and reading comprehension at SMAN 3 Baubau. The aim of the research is to find out whether there is a significant relationship between reading anxiety and reading comprehension at SMAN 3 Baubau. This research is quantitative research. The population in this study was all class XI, totaling 95 students. The sample was taken using a side random technique, totaling 30 students, consisting of 3 classes, namely class XI Merdeka 1, XI Merdeka 2, XI Merdeka 3. Data collection in this research was carried out using research instruments in the form of questionnaires and tests, to determine the effect of reading anxiety on reading comprehension in the use of English. The data obtained was analyzed using descriptive statistical analysis, prerequisite analysis, and inferential statistical analysis. Based on the research results, it was concluded that there was no significant relationship between reading anxiety and reading comprehension. This conclusion is based on statistical analysis. Because Fcount is 0.307 with a significance value of 0.584, Fcount is lower than Ftable and the significance value is greater than (0.05). This means that the hypothesis H0 is accepted and the alternative hypothesis is rejected.